The Jews and modern capitalism - Sombart, Werner (Transaction books, 1951)
Exact facsimile of the original edition, not reproduced with Optical Recognition Software. Werner Sombart (1863 -1941) was a German economist and sociologist and one of the leading Continental European social scientists during the first quarter of the 20th century. Sombart's "The Jews and Modern Capitalism" is an effort similar to Max Weber's historic study of the connection between Protestantism (especially Calvinism) and Capitalism, with Sombart documenting Jewish involvement in historic capitalist development. He argued that Jewish traders and manufacturers, excluded from the guilds, developed a distinctive antipathy to the fundamentals of medieval commerce, which they considered primitive and unprogressive. They tended to reject the medieval desire for 'just' (and fixed) wages and prices, a system in which shares of the market were agreed upon and unchanging, profits and livelihoods modest but guaranteed, and limits placed on production.